(untitled) (Research, Society and Development, 2020)
The present study aimed the viability evaluation of solid intramedullary rods made with polyamide 12 and coated with hydroxyapatite in experimentally osteotomized humerus of young roosters (white Plymouth rock). Sixteen animals of 45 days old each were used. After general anesthesia, they underwent to complete transverse osteotomy of the right humerus diaphysis to implant the already described rods which filled the entire length of the medullary cavity and were fixed by two cortical stainless steel screws in each bone fragment. The surgical technique was well succeeded without any trans-operative intercurrence. Through clinical and radiographic examination, it was observed that soon after the anesthesia recovery, six rods (37,5%) broke next to the fracture focus and the same was noticed with the others (62,5%) on seventh day post-surgery. Based on the obtained results, it can be hypothesized that polyamide 12 rods resistance could have been affected by all the thermal stages necessary to its incorporation with hydroxyapatite. Furthermore, the roosters’ age may also have contributed to adverse outcomes. However, future researches will be necessary to confirm those hypotheses.